Influence of lisinopril on cardiac remodeling induced by tobacco smoke exposure - Duarte, Daniella R. [UNESP]; Minicucci, Marcos F. [UNESP]; Azevedo, Paula S. [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Matsubara, Beatriz B. [UNESP]; Matsubara, Luiz S. [UNESP]; Campana, Álvaro O. [UNESP]; Paiva, Sergio A. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP] (My University, 2010)
Background: To investigate the effect of lisinopril on cardiac remodeling induced by smoking. Material/Methods: Rats were allocated into 3 groups: group CON (n=8): control; group CSE (n=8): cigarette smoke exposure; group CSE-LIS (n=8): exposed to tobacco smoke and treated with lisinopril. Results: After 2 months, the tail systolic pressure was lower in CSE-LIS (CON=116 ±27 mm Hg, CSE=126±16, CSE-LIS=89±12; P<.001). CSE animals showed higher left ventricular systolic diameter (CON=8.25±2.16 mm/kg, CSE=11.5±1.3, CSE-LIS=9.27±2.00; P=.009) and myocyte cross-sectional area (CON=245±8 μm2, CSE=260±17, CSE-LIS=238±12; P=.01) than CON and CSE-LIS. The ejection fraction (CON =0.91±0.02, CSE=0.86±0.02, CSE-LIS=0.92±0.03; P=.002) and fractional shortening (CON=55.7±4.41%, CSE=48.7±3.43, CSE-LI=58.2±7.63; P=.006) were lower in CSE group than CON and CSE-LIS. CSE and CSE-LIS animals showed higher collagen amounts (CON=3.49±0.95%, CSE= 5.01±1.58, CSE-LIS=5.27±0.62; P=.009) than CON. CON group showed a higher connexin 43 amount in the intercalated disc (CON=3.70±0.38, CSE=2.13±0.53; CSE-LIS=2.17±0.73; P=.004) than CSE and CSE-LIS. There were no differences in IFN-g or TNF-a cardiac levels among the groups. Conclusions: Lisinopril attenuated both morphologic and functional abnormalities induced by exposure to tobacco smoke. In addition, this effect was associated with diminished blood pressure, but not alterations in connexin 43 distribution, cytokine production or collagen amount. © Med Sci Monit, 2010.
Keywords: Heart failure; Hypertrophy; Smoking; Ventricular function